KAJIAN DOMAIN-DOMAIN INDEKS PEMBANGUNAN PEMUDA: ARAH PEMBANGUNAN KEPEMUDAAN DI JAWA BARAT - Syhabuddin Al-Tapsi; Teuku Soedono Sasmoyo Janapriya (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2025)
The consistent low value of the Youth Development Index (IPP) in West Java Province reflects several strategic issues, including the competitiveness of the young workforce, disparities in the quality of human resources, inequality between regions, slowing economic growth, and governance optimization. Location Quotient (LQ) and Shift Share approaches were used to analyze secondary data on IPP domains and values from 2019 to 2023. This study aims to identify and analyze the strengths and competitiveness of each domain constituting the IPP in West Java. The results show that although the education domain has the largest impact on the national IPP value, along with the employment and job opportunities and participation and leadership domains, all three domains still face the challenge of slow growth and insufficient competitiveness. In contrast, strengths lie in the gender and discrimination domain and the health and well-being domain, which show significant progress. This study has complemented the analysis of competitiveness across IPP domains, a topic that has been underexplored, thereby providing a deeper understanding of the competitive landscape among IPP domains.